2014
DOI: 10.1007/978-3-319-11845-1_30
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality, Product Quality and Service Recovery as Antecedents of Client Satisfaction in a Business-to-Business Context: An Empirical Study

Abstract: The advent of Relationship Marketing and the increasing competition characterizing the markets of the last 30 years placed the conceptualization and measurement of the quality and satisfaction variables in the center of modern marketing theory and practice as principal indicators of marketing performance (Babin and Griffin 1998; Walker 1995; Jones and Suh 2000). During the last years, we were pilot of an increasing process of globalization in the world. Thus, we see that the traditional definitions of markets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…During the past few decades, there has been tremendous efforts to learn the effects of different variables including price, quality, brand, etc. on consumers' purchase intention (Castro & Marques, 2017;Chumpitaz et al, 2014;Kalaignanam et al, 2017). Karnreungsiri and Praditsuwan (2017), for instance, investigated the factors influencing buying behavior and buying decision process of customers and found that price was one of the influencing factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few decades, there has been tremendous efforts to learn the effects of different variables including price, quality, brand, etc. on consumers' purchase intention (Castro & Marques, 2017;Chumpitaz et al, 2014;Kalaignanam et al, 2017). Karnreungsiri and Praditsuwan (2017), for instance, investigated the factors influencing buying behavior and buying decision process of customers and found that price was one of the influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…In order to persuade the customers to become interested in purchasing a product, it is necessary to analyse the factors that influence the customer interest (Ambarwati & Dwijanto, 2015;Chumpitaz et al, 2014;Kalaignanam et al, 2017;Simpursiah, 2015;Sundalangi et al, 2014;Zhahir & Widayanto, 2018). Some researchers have analyzed the customer interest in the form of product quality (Rusmawan, 2014), brand image (Lukman, Adree, & Setiawan, 2013;Masyhuri & Magnadi, 2016;Ratnasari et al, 2014;Setyaningrum & Wijayanto, 2014;Faradila & Soesanto, 2016),and price (Adiputra & Sutopo, 2016;Castro & Marques, 2017;Rokim et al, 2014;Amanda & Mudiantono, 2015;Anggi & Soesanto, 2016).…”
Section: Introductionmentioning
confidence: 99%